APLIKASI GKI-CITRA BERBASIS IOS STUDI KASUS DI GEREJA KRISTEN INDONESIA PERUMAHAAN CITRA - Kevin R Oktavian; Teddy Marcus Zakaria (Duta Wacana Christian University, 2016)
Provision of information to the church as the church bulletin, paideia, pastoral message, activities and schedule of activities on the Indonesian Christian Church - Perumahan Citra 1 was still done manually. Therefore, we need a system that can help these people to get the information easily, quickly and at any time. Previously, an Android application have been developed to provide information automatically. Considering that not all users are using Android, this research aimed at developing iOS application that will add to the current applications available. This system has several features, giving the church bulletin information, paideia, pastoral message, activities, schedule events, activities and schedule of data processing activities do content approval. Hopefully with this iOS-based applications will supplement the existing system on the Indonesian Christian Church - Perumahan Citra..